855. Impact of FDA Black Box Warning on Fluoroquinolone and Alternative Antibiotic Use in Southeastern US Hospitals. (26th November 2018) - Yarrington, Michael; Anderson, Deverick J; Ashley, Elizabeth Dodds; Jones, Travis; Johnson, Melissa; Lokhnygina, Yuliya; Sexton, Daniel; Moehring, Rebekah W
Abstract: Background: Many antimicrobial stewardship programs have set goals to reduce the use of fluoroquinolones because of risks of causing C. difficile and other adverse safety events. The US Food and Drug Administration issued a black box label warning for fluoroquinolones in June 2016 recommending avoidance of this class for treatment of uncomplicated infections. Methods: We performed a retrospective cohort study of antimicrobial use (AU) data in 29 southeastern United States hospitals from 2013 to 2017. An interrupted time series approach with segmented negative binomial regression modeling was used to estimate the longitudinal trend and effect of the FDA safety announcement on AU rates. Fluoroquinolone and alternative antibiotic agent use rates were measured as days of therapy (DOT) per 1, 000 patient days. Alternative antibiotics were analyzed individually or in groups (e.g., community-onset agent group included ceftriaxone, cefotaxime, and ertapenem). Results: Hospital AU data for the 60-month period included a total of 6, 685, 950 patient days; 8 to 29 hospitals contributed AU data to estimates each month. FQ use rates declined at a consistent rate of approximately 1 DOT/1, 000 patient days per month resulting in an overall 10% decrease prior to the FDA warning. A significant drop in FQ use rates occurred at the time of the announcement ( P = 0.002), but there was no significant change in trend [rate ratio (RR) 0.89, 95% CI 0.79–1.01, P = 0.07, Figure 1]. Alternative antibiotic use significantly increased for the following antibiotic groups after the warning: community-onset agents (RR 1.24, 95% CI 1.11–1.38), atypical agents (RR 1.40, 95% CI 1.19–1.66), and third-generation cephalosporins (RR 1.54, 95% CI 1.19–1.65). Antipseudomonal β-lactam use remained stable (RR 0.96, 95% CI 0.88–1.05, P = 0.3). Conclusion: Fluoroquinolone use was declining in our network prior to the FDA announcement and continued to decline after 2016. This is likely due to stewardship activities focusing on quinolone-sparing treatment guidelines. AU shifted away from FQ toward third-generation cephalosporins and atypical agents. Disclosures: All authors: No reported disclosures.